A megaraptorid (Dinosauria: Theropoda) frontal from the upper Strzelecki Group (Lower Cretaceous) of Victoria, Australia - Kotevski, J.; Duncan, R.J.; Pentland, Adele; Rule, J.P.; Vickers-Rich, Patricia; Rich, T.H.; Fitzgerald, E.M.G.; Evans, A.R.; Poropat, Stephen (2024)
Cretaceous (non-avian) theropod dinosaurs from Australia are poorly understood, primarily because almost all specimens described thus far comprise isolated postcranial elements. In Australia, only three non-dental cranial elements pertaining to Theropoda have been reported: the left and right dentaries of Australovenator wintonensis from the Winton Formation (Cenomanian–lowermost Turonian) of Queensland, and an isolated surangular from the Eumeralla Formation (lower Albian) of Victoria. Herein, we report the first evidence of non-mandibular cranial material of a non-avian theropod from Australia: a left frontal and fused parietal fragment from the Lower Cretaceous (lower Aptian) upper Strzelecki Group of Victoria. The specimen shares several synapomorphies with the frontals assigned to Megaraptoridae, including an anteroposteriorly elongate postorbital articulation and a truncated nasal articular surface. Accordingly, we regard this frontal as Megaraptoridae gen. et sp. indet. We performed both parsimony-based and Bayesian-based phylogenetic analyses to support our assignment, and both analyses support a placement within Megaraptoridae. However, this specimen appears to possess plesiomorphic characters relative to other megaraptorid frontals, lacking dorsoventrally high walls of bone that emarginate the nasal and prefrontal articular surfaces. The plesiomorphies of this specimen have implications for the evolution of the megaraptoran skull roof, suggesting the acquisition of specialised adaptations for longirostry over time. This specimen improves the limited record of Cretaceous Australian theropod cranial remains, and provides limited support for the hypothesis that Megaraptoridae might have originated in Australia.